TANGGUNG JAWAB PENDIDIK TERHADAP PENDIDIKAN FISIK DAN PSIKIS ANAK DALAM ISLAM - Fu’ad Arif Noor (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2017)
The meaning of the term is “ready to accept responsibility or duty obligations”.The sense of responsibility that should be very easy to understand by everyone. Butif asked to do so in accordance with the earlier definition of responsibilities, thereis often still find it hard, had a problem, there are even people who feel inadequateif given him a sense of responsibility. Most people dodge responsibility, because it'smuch easier to avoid responsibility, rather than accept responsibility. Many peopledodge responsibility, because it's easier to shift responsibility, rather than stand upboldly and declare unequivocally that, It's my responsibility. Many people are veryhappy with the throwing shoulder its responsibilities to other people.Hence came a proverb, hidden stone throwing hand. A proverb that mean someone who does not dare to be responsible for his own behavior, so he let others bearthe burden of responsibility. Could also be interpreted as some one who escaperesponsibility, and love looking for scapegoats to save himself from actions thatharm others. Some people, because they can not understand the meaning ofresponsibility; often in his life very fond of self-defense with the words, It was notmy fault. Too many people are in vain, to spend time to avoid responsibility byblaming the other person, rather than to accept responsibility, and bravely face anychallenge in front of him.Many events in this country, which is caused by people who are not responsible,instead often won or excessive relief granted by the environment with highlyimplausible. It's very sad. At the present time, many people who dodgeresponsibility, because they have gained from that attitude. More teragis again, offthat responsibility is often supported by a nearby neighborhood, his friends, hischildren, his boss, his son, even supported by his wife or her husband. Can be seen,for example, corruption, and manipulation. Most of the people in the nearbyenvironment were supportive, because they are all bound to feel the results of it'scorruption or manipulation. Prophet Muhammad Prophet's sayings: Everyone ofyou is a leader, and you are responsible for the leadership ". (Al-Hadith, SahihBukhari - Muslim).